OPTIMIZATION OF HYDROGEN FUEL CELL – REVIEW (International Journal of Food and Nutritional Sciences, 2022)
Abstract— A fuel cell is an electro-chemical instrument that generate’s electricity by using Hydrogen and Oxygen. A catalyst is used in a fuel cell to divide hydrogen into electrons and protons, which are then sent via an external circuit to generate electricity.The different types of fuel cell are:1) PEMFC - Proton Exchange Membrane Fuel Cell2) DMFC- Direct Methanol Fuel Cell3) PAFC- Phosphoric Acid Fuel Cell4) AFC- Alkaline Fuel Cell5) MCFC- Molten Carbonate Fuel Cell6) SOFC- Solid Oxide Fuel CellThe fuel cell chosen for optimization, PEMFC, Proton Exchange Membrane Fuel Cell, is a future of forthcoming energy source due to its benefits of high energy output, low operating temperature, and zero pollution, which may be achieved by the following techniques. Increasing the electrode area, using catalysts, and boosting the temperature are all options.As an electrolyte, the fuel cell employs a water-based acidic polymer membrane with a platinum electrode. This fuel cell operates at a low operating temperature (below 100 degrees Celsius) and may create electrical output based on power requirements. Because of the low operating temperature and the usage of noble metal electrodes, the fuel cells must run on pure hydrogen . PEMFC cell is the dominating technology for vehicle and material handling vehicle applications, but it is not widely employed in other applications.The high temperature PEM fuel cell is a PEM fuel cell variation with a higher working temperature (HT PEM fuel cell). This fuel cell can run at temperatures up to 200 degrees Celsius by employing mineral acid-based electrolyte rather than water-based electrolyte. By implementing the following, the fuel cell is able to operate in the presence of larger levels of impurity in the fuel.